Profil Sosial Ekonomi Petani Cengkeh di Desa Umpungeng Kecamatan Lalabata Kabupaten Soppeng - Suwarni Suwarni (UNIVERSITAS NEGERI MAKASSAR, 2022)
AbstractThis study aims to determine the socio-economic description of clove farmers, and to determine the direction and form of clove farmer household investment in Umpungeng Village, Lalabata District, Soppeng Regency. This research is a descriptive research. Sources of data obtained by respondents from 66 households. Data collection in this study was carried out using observation and documentation techniques. The data obtained were then analyzed by descriptive analysis techniques. The results of the research on socio-economic conditions showed that the level of education was low as much as 34.85% did not finish elementary school, the number of household members and the average dependent load was 3-7 people. and side livelihoods include cocoa farmers, coffee farmers, entrepreneurs, carpenters, honorary employees, and civil servants, clove farmer households as many as 66 respondents were declared not poor 100%, the average capital was > Rp. 1,500,000 - 2,000,000 with a land area of 1 hectare. The results of the direction and form of clove farmers' investment, namely the sale of cloves, are invested for household development, savings, and gold. Other forms of investment include human resource development, worship development, and business development.AbstrakPenelitian ini bertujuan untuk mengetahui gambaran sosial ekonomi petani cengkeh, dan untuk mengetahui arah dan bentuk investasi rumah tangga petani cengkeh di Desa Umpungeng Kecamatan Lalabata Kabupaten Soppeng. Penelitian ini merupan penelitian deskriptif. Sumber data diperoleh responden 66 rumah tangga. Pengumpulan data dalam penelitian ini dilakukan dengan teknik observasi, dan dokumentasi. Data yang diperoleh selanjutnya dianalisis dengan teknik analisis deskriptif. Hasil penelitian kondisi sosial ekonomi menujukkan tingkat pendidikan rendah sebanyak sebanyak 34,85 % tidak tamat SD, jumlah anggota rumah tangga dan beban tanggungan rata-rata 3-7 orang. dan mata pencaharian sampingan meliputi petani kakao, petani kopi, pengusaha, tukang kayu, pegawai honor, dan Pegawai Negeri Sipil, rumah tangga petani cengkeh sebanyak 66 responden dinyatakan tidak miskin 100%, rata-rata menggunakan modal sebesar > Rp.1.500.000-2.000.000, luas lahan yang digunakan 1 Ha. Hasil arah dan bentuk investasi petani cengkeh yaitu penjualan cengkeh di investasikan untuk pengembangan rumah tangga, tabungan, dan emas. Adapun bentuk investasi lainnya berupa pengembangan sumber daya manusia, pengembangan ibadah, dan pengembangan usaha.